Safety Education through Risk Analysis in the Printing Informal Sector - Ahlunijar, Rega; Wahid, Ayu Fadilah; Akmal, M. Aulia Farhan; Rengganis, Caroline Kirana Christi; Karuniawati, Suci; Kholim, Howen (Universitas Negeri Semarang, 2023)
The printing industry is one of the most informal industries in university environments, such as in Universitas Negeri Semarang which has many printers, ranging from printing books to banners. The printing industry is not free from risks of danger, even though it is only in a small sector, but all workplaces have their own risks of danger. The method used in this research was descriptive research. Analysis was carried out by collecting data through field observations and analysis using JSA. The population and sample in this study were 10 workers in three printing houses in the Universitas Negeri Semarang area. There are a total of 6 routine work processes carried out by workers in the printing industry with 38 hazards identified. The highest intensity risks were found in muscle, bone and skeletal disorders as well as skin irritation and respiratory problems. This was because when working the position of the worker was not ergonomic and the work involved chemicals in the form of ink. The recommended improvement for printing owners is the use of APB to minimize risks arising from identified hazards such as wearing masks to reduce exposure to chemical vapours.